Beyond therapy? Investigating biomedical enhancement in the case of human growth hormone - Morrison, Michael (2008)
This project is an investigation of the issue of human biomedical enhancement, taking human growth hormone as a case study. Growth hormone is mainly used to increase the adult height of short children, and is also employed illicitly as an anti-ageing treatment. Both these applications are viewed by bioethicists as going beyond the scope of therapeutic medicine by enhancing normal human traits rather than treating diseases and as such are considered ethically suspect. This project adopts a comparative and retrospective stance, examining the socio-historical development of human growth hormone in the US, where much of the impetus for enhancement uses has originated, and also in the UK where the potential for enhancement uses of pharmaceuticals and other medical technologies is a growing concern.